Transformations of the 2,7-Seco aspidosperma alkaloid leuconolam, structure revision of epi-Leuconolam, and partial syntheses of leuconoxine and leuconodines A and F - Kam, T.S.; Low, Y.Y.; Hong, F.J.; Lim, K.H.; Thomas, N.F. (American Chemical Society, 2013)
Several transformations of the seco Aspidosperma alkaloid leuconolam were carried out. The based-induced reaction resulted in cyclization to yield two epimers, the major product corresponding to the optical antipode of a (+)-meloscine derivative. The structures and relative configuration of the products were confirmed by X-ray diffraction analysis. Reaction of leuconolam and epileuconolam with various acids, molecular bromine, and hydrogen gave results that indicated that the structure of the alkaloid, previously assigned as epi-leuconolam,was incorrect. This was confirmed by an X-ray diffraction analysis, which revealed that epi-leuconolam is in fact 6,7-dehydroleuconoxine. Short partial syntheses of the diazaspiro indole alkaloid leuconoxine and the new leuconoxine-type alkaloids leuconodines A and F were carried out.